DEVELOPING BIG BOOK AS MEDIA FOR TEACHING ENGLISH AT THE THIRD GRADE STUDENTS OF ELEMENTARY SCHOOL IN SD LABORATORIUM UNDIKSHA SINGARAJA IN ACADEMIC YEAR 2017/2018 - ., Ketut Andi Wiraprasta; ., Prof. Dr. Putu Kerti Nitiasih, M.A.; ., Ni Wayan Surya Mahayanti, S.Pd.,M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
Wiraprasta, K. A1, Nitiasih, P. K2, Mahayanti, N. W. S3 123English Education Department Ganesha University of Education Singaraja, Indonesia andiwiraprasta94@gmail.com, titiekjegeg@gmail.com, mahayantisurya@yahoo.co.id Abstrak Tujuan dari penelitian ini adalah untuk (1) mengembangkan big book sebagai media pemeblajaran untuk kelas tiga sekolah dasar di SD Laboratorium UNDIKSHA Singaraja, (2) mengetahui kulitas big bookyang dikembangkan. Subjek dari penelitian ini adalah 35 siswa kelas tiga sekolah dasar di SD Laboratorium UNDIKSHA Singaraja. Data dari penelitin ini didapat menggunakan lembar observasi, panduan wawancara, kuesioner, ceklist, rubric, catatan, dan test. Research ini adalah penelitian pengembangan yang menggunakan Sugiyono sebagai model, ada beberapa prosedur dalam Sugiyono yaitu identifikasi potensi dan masalah, pengumpulan data, mendisain produk, revisi produk, iji coba produk, dan revisi produk. Ada empat big book yang dikembangkan sebagai media untuk mengjar bahasa Inggris dengan tema makanan & Minuman, buah & sayuran, Keluarga, dan anggota tubuh. Masing-masing big book terdiri dari 13 sampai 15 halaman dan mengandung karakter pendidikan di masing-masing buku. Dan kualitas produk, ditemukan bahwa big book dikategorikan sebagai media yang sangat bagus dari dua ahli, dan dikategorikan sebagai media yang baik dari kuesioner guru. Sehinggga big book cocok digunkan untuk mengajar bahasa inggris untuk kelas tiga sekolah dasar. Kata Kunci : big book, pendidikan karakter, anak-anak Abstract The aim of this research was to (1) developed big book as media for teaching English at the third grade students in SD Laboratorium UNDIKSHA Sinagaraja, and (2) find out the quality of big book developed. The subject of this research was thirty-five students at third grade students of elementary school at SD Laboratorium UNDIKSHA Singaraja. The data of this research were obtained by using observation sheet, interview guide, questionnaire, checklist, rubric, notes and test. The research was Research and Development research which was used Sugiyono as model of the research, there are several procedure on Sugiyono model namely identifying potency and problem, collecting data, designing product, revising product, validating product, trying-out product, and revising product. There were four big book developed as media for teaching English with the theme food & drink, fruit & vegetables, my family, and body part. Each book consisted of thirteen up to fifteen pages and was inserted character education in each big book. And the quality of the product, it was found that the big book was categorized as excellent media from the two expert judgements and was categorized as good media from the teacher questionnaire. It means, big book was proper to be used as media for teaching English at the third grade students of elementary school. keyword : big book, character education, young learners